KONSEP PENEGAKKAN HUKUM TERHADAP WAJIB PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN DALAM RANGKA MENGOPTIMALKAN PENCAPAIAN PENDAPATAN ASLI DAERAH - Musdalipa (Universitas Tadulako, 2024)
The aim of this research is to analyze the concept of law enforcement for rural and urban land and building tax payers, to analyze the collection of land and building tax in rural areas to optimize local revenue in Central Mamuju Regency and to analyze the legal aspects of the smoke innovation policy. The research method uses normative legal research, using a statutory approach, a conceptual approach. Sources of legal materials come from primary, secondary and tertiary legal materials. The research results obtained conclusions 1). In the Law Enforcement Concept for Rural and Urban Land and Building Taxpayers, the Regional Government applies sanctions in the form of interest/fines of 2% per month. In terms of the imposition of criminal acts in the field of regional taxation, it will only be carried out as a final measure when people do not comply with taxes, in this case the regional government prioritizes the principle of Ultimum Remidium. 2) Law Enforcement Efforts carried out by the Central Mamuju Regency Government Cq. BPKPAD, in terms of increasing Regional Revenue Optimization, has provided extraordinary results where the realization or receipt of Regional Taxes, especially PBB-P2, has increased significantly. 3) Legal Aspects of the SMOKE INNOVATION Policy. Efforts to increase Mamuju Regency's original regional income, namely with Law Number 30 of 2014 and Government Regulation Number 38 of 2017 and Regional Regulation Number 8 of 2023.